Potential Regional Economic Development Strategy of Sota Border - Samel W. Ririhena; Fenty Y. Manuhuttu; Marthen A. I. Nahumury; Alexander Phuk Tjilen (International Journal of Social Science and Business, 2023)
Sota District has very rich natural potential so that it can be developed as a source of the community's economy. To create a prosperous society, a strategy for developing economic potential is needed. Based on this, this study aims to analyze the strategy for developing economic potential in the Sota Border area. The type of research used is descriptive qualitative with interview and documentation data collection methods. The data analysis used is triangulation. The results of the study show that the strategies found in Sota Regency for the development of economic potential include: 1) optimizing and controlling the use of natural resources; 2) accelerating the development of economic infrastructure and improving the investment climate at land borders, spatial planning in land border areas, accelerating the construction of facilities and infrastructure for Sota Cross Border Posts (PLBN); and 3) increasing the strength of human resources through the empowerment process for developing productive community business activities, developing cross-border trade and sub-regional economic and tourism cooperation with the aim of changing behavior and creating self-reliance. The implication of this research is the need for the role of government and experts in optimizing strategies to develop economic potential.